Control the crosslinking of epoxy-asphalt via induction heating. Issue Volume 21:Issued 8(2020) (2nd July 2020) - Apostolidis, Panos; Liu, Xueyan; van de Ven, Martin; Erkens, Sandra; Scarpas, Tom
ABSTRACT: Induction heating driven polymerisation is an in-situ curing technique for epoxy-asphalt systems that maintains most of the advantages of temperature-driven polymerisation and it solves the need for longer curing time periods at lower temperatures before traffic can be allowed. In particular, induction heating can be utilised to accelerate the polymerisation of paving mixes with a thermo-hardening nature. In this study, steel fibres are dispersed in a mix and during exposure to an alternating electro-magnetic field generated by induction coils, they are heated leading to the rapid initiation of epoxy-asphalt polymerisation. This research presents the implementation of a finite element model analysis for assessing the potential of utilising steel fibres for the development of inductive mixes with sufficient induction heating efficiency. A produced and compacted mix with steel fibres was reconstructed by means of CT scans on samples from the mix and its effective electrical conductivity was calculated. Also, the electro-magnetic induction-driven polymerisation of epoxy-asphalt is simulated by extending a model developed elsewhere. The extended method can be used to predict the evolution of the curing process, and further of mechanical properties thereby indicating that electro-magnetic induction represents a reliable polymerisation method to cure epoxy-asphalt systems.